EZH2-mediated PP2A inactivation confers resistance to HER2-targeted breast cancer therapy - Yi Bao (Nature Portfolio, 2020)
Resistance to anti-HER2 therapies in breast cancer remains a significant clinical challenge. Here, the authors demonstrate that EZH2 regulates response to HER2-targeting therapies in breast cancer, in part, by modulating the expression of PPP2R2B.